Septic systems contribute artificial sweeteners to streams through groundwater - John Spoelstra; Sherry L. Schiff; Susan J. Brown (Journal of Hydrology X, 2020)
Artificial sweeteners are ubiquitous constituents of sanitary wastewater and are not completely attenuated by wastewater treatment processes. Consequently, artificial sweeteners are increasingly employed as a tool to detect wastewater and help evaluate its impact on aquatic environments. In rural areas, septic systems are known point sources of artificial sweeteners to groundwater, however the potential contribution of artificial sweeteners to streams via this pathway is unknown. We analyzed 294 samples from 173 stream sites in Southern Ontario, Canada, for acesulfame, saccharin, cyclamate, and sucralose, and found that 91% had one or more of these compounds present. The stream sites sampled did not have municipal wastewater treatment plants upstream and therefore septic system effluent was the most likely source of the artificial sweeteners. Acesulfame, which is the most recalcitrant of the four artificial sweeteners, was by far the most ubiquitous in streams, with a 91% detection frequency, compared to 27, 8, and 3% for saccharin, cyclamate, and sucralose, respectively. Stream concentrations ranged from non-detectable to maximum values of 225, 380, 204, and 291 ng/L for acesulfame, saccharin, cyclamate, and sucralose, respectively. We calculated that water from septic effluent contributed from <0.005% to 0.5% of streamflow, with a median value of 0.052%. This is the first study to use artificial sweetener concentrations to quantify the fraction of septic effluent reaching streams via groundwater flow. Using acesulfame concentrations, we calculated that approximately 13% of the septic effluent water generated in rural Southern Ontario eventually ends up in local streams, however this is likely a conservative estimate. Although much of the septic effluent water that reaches streams may be free of all but the most persistent anthropogenic compounds, our study demonstrates that domestic wastewater must be considered as a possible source of stream contaminants, even if municipal wastewater is not a factor in the watershed.